Analysis on The Substitution Ability of Mocaf Flour Toward Wheat Flour, its Business Feasibility, and its Industry Multiple Effects - Muhammad Riza Firdaus; Widyarfendhi .; Rusniati .; Novita Weningtyas Respati (Journal of Wetlands Environmental Management, 2017)
The production of mocaf flour in MSME scale in South Kalimantan area was not feasible considered from its business feasibility hence the multiple effect was unmeasured based on its industry existence. Mocaf flour production derived from cassava, which is a plant that not only match on dry land but also in the wetlands of South Kalimantan, can not be oriented consumer as a substitute for wheat flour for common food products in the society. Therefore, further research refers to aspects mocaf flour premium for health. This objective of this research was to increase the society consumption of mocaf flour for the healthy reason related to the trend on negative effect from high level of gluten in wheat flour. The laboratory test showed the result that supports mocaf product for health. With this consideration then mocaf processed product have potentials to bedeveloped though serious marketing effort is required due to infamiliarity of the mocaf flour especially in South Kalimantan area. Difference test result showed that prospects, indeed, haveintention to purchase mocaf-based processed products for healthy reason.